2022
DOI: 10.1155/2022/1384471
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Sema4D Level Is Positively Correlated with Sema4D Expression in PBMCs and Peripheral Blast Number in Acute Leukemia

Abstract: Semaphorin 4D (Sema4D) is highly expressed in various cancers and leukemia. It is involved in the development of acute leukemia. A high level of soluble Sema4D is also present in the plasma of acute leukemia patients. However, it remains unknown whether Sema4D is associated with the clinical characteristics of acute leukemia. In this study, Sema4D expression was examined in peripheral blood mononuclear cells (PBMCs) and bone marrow mononuclear cells (BMMCs) of patients with acute leukemia, and it was highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Sema4D was highly expressed in patients with BCP-ALL, TCP-ALL, and AML compared to controls. There was a positive correlation between Sema4D levels in PBMCs and in serum ( p = 0.0249), and between Sema4D levels in PBMCs, and the leukocyte count ( p = 0.0002) and the peripheral blast number ( p = 0.0036) [ 106 ]. As per the study conducted by Jian et al [ 105 ], it was not observed that the difference in Sema4D expression varied according to the cell type.…”
Section: Prognostic Biomarkers For Bcp-allmentioning
confidence: 99%
See 1 more Smart Citation
“…Sema4D was highly expressed in patients with BCP-ALL, TCP-ALL, and AML compared to controls. There was a positive correlation between Sema4D levels in PBMCs and in serum ( p = 0.0249), and between Sema4D levels in PBMCs, and the leukocyte count ( p = 0.0002) and the peripheral blast number ( p = 0.0036) [ 106 ]. As per the study conducted by Jian et al [ 105 ], it was not observed that the difference in Sema4D expression varied according to the cell type.…”
Section: Prognostic Biomarkers For Bcp-allmentioning
confidence: 99%
“…That pattern was also observed in vivo and correlated with the level of expression. It is assumed that Sema4D plays a crucial role in leukemia development by regulating the PI3k/AKT and ERK signaling pathways and may be a biomarker for ALL prognosis [ 105 , 106 ].…”
Section: Prognostic Biomarkers For Bcp-allmentioning
confidence: 99%